Start, czyli powrót. Wokół Międzywojnia Jana Brzękowskiego - Wójtowicz, Aleksander (Śląskie Studia Polonistyczne, 2013)
Międzywojnie (1982) by Jan Brzękowski is a novel situating itself in the current of the “genealogy of avant-garde”. The writer, like other authors from the circle of the First Avant-garde, returns to his youth times, though the very return is determined by not only a nostalgic impulse, but also certain bitterness, deriving from the impossibility to find a place in the literary environment in emigration. Międzywojnie is at the same time a summary of his experiences and artistic achievements so far. The first part of the work, entitled Start is a flourishingly outlined portrait of generation entering adulthood alongside gaining independence by Poland, and a peculiar spiritual biography showing the basis of experiences of generation from which the authors from the circle of the “Nowa Sztuka” came. The second part, on the other hand, Collegium Novum, constitutes the continuation of earlier prose experiments by Brzękowski who, returning to strategies and solutions proposed a few decades earlier, wanted to underline not only their significance, but also up-to-dateness.